Risk management to improve the quality of higher education institutions using a risk map (Gumilyov Journal of Pedagogy, 2026)
The article examines the importance and relevance of the risks faced by universities in the activities of the university and examines the management of identified risks using a risk map. The authors analyzed the state of risk awareness in the domestic and foreign scientific and pedagogical literature.  In order to determine the significance of the risks encountered at the university, many types of risks are differentiated. University risk management should be based on generally accepted approaches, educational features, and a specific classification of risks and risks of the university. Higher education is an area characterized by certain risks. The definition, forecasting and assessment of risks of the educational organization should be carried out in the context of the quality of training of students, comply with approved quality goals, as well as established norms and requirements of educational standards. At the same time, it is important to evaluate the activities of the university in terms of providing the necessary resources. The relevance of risk management in educational institutions is due to the reform of the higher education system. In this regard, there is a need to identify and assess the risks and opportunities of educational organizations, as well as to search for new methods of their management. The purpose of the article is to manage internal and external types of risks encountered in the activities of higher education institutions using a risk map. Within the framework of the article, internal and external factors affecting the activities of the university were considered.